An introduction to the hows and whys of molecular typing - Farber, J.M. (Health Canada, Ottawa, Ontario, Canada.) (Journal of food protection, 1996)
Until recently, the relatedness of bacterial isolates has been determined solely by testing for one or several phenotypic markers, using methods such as serotyping, phage typing, biotyping, antibiotic susceptibility testing, and bacteriocin typing. However, there are problems in the use of many of these phenotype-based methods. For example, phage and bacteriocin typing systems are not available for all bacterial species and serotyping can be labor-intensive and costly. In addition, phenotypic markers may not be stably expressed under certain environmental or culture conditions. In contrast, some of the newer molecular typing methods involving the analysis of DNA offer many advantages over traditional techniques. One of the more important advantages is that since DNA can always be extracted from bacteria, all bacteria should be typeable. Another is that the discriminatory power of DNA-based methods is greater than that of phenotypic procedures. This review focuses on the basics of molecular typing along with the advantages and disadvantages of several of the newer genotypic typing techniques. This includes methods such as plasmid typing, pulsed-field gel electrophoresis, ribotyping and its variations, and polymerase chain reaction-based methods such as random amplified polymorphic DNA analysis. Molecular typing of microorganisms has made great strides in the last decade, and many food microbiology laboratories have become more knowledgeable and better equipped to carry out these new molecular techniques. Molecular typing procedures can be broadly defined as methods used to differentiate bacteria, based on the composition of biological molecules such as proteins, fatty acids, carbohydrates, etc., or nucleic acids. The latter can also be more specifically defined as genotyping, and is the subject of this review